The Category of ‘Ethical Apophaticism’ in Modern Orthodox Theology - Torrance, Alexis (International journal of systematic theology, 2021)
This article begins by summarizing the concept of ethical apophaticism in the theology of John Zizioulas and Christos Yannaras. The impetus for this concept, namely a desire to maintain the irreducibility of the human person to extrinsic ethical categories, is noted and celebrated. However, it is proposed that to do fuller justice to the understanding of the ethical and moral life in the Orthodox tradition, a certain ‘ethical cataphaticsm’ needs to be brought into the discussion. Some potential lineaments of what this might entail for these authors are highlighted (repentance and love) before seeking to supplement them with a discussion of the commandments of Christ through the lens of the theology of Sophrony Sakharov. It is argued that Christ’s commandments provide the sure path to developing an ethical cataphaticism that can work in tandem with the insights of the category of ethical apophaticism offered by Zizioulas and Yannaras.